Neoangiogenesis-related genes are hallmarks of fast-growing hepatocellular carcinomas and worst survival. Results from a prospective study. Issue 5 (9th February 2015) - Villa, Erica; Critelli, Rosina; Lei, Barbara; Marzocchi, Guido; Cammà, Calogero; Giannelli, Gianluigi; Pontisso, Patrizia; Cabibbo, Giuseppe; Enea, Marco; Colopi, Stefano; Caporali, Cristian; Pollicino, Teresa; et al.
Abstract : Objective: The biological heterogeneity of hepatocellular carcinoma (HCC) makes prognosis difficult. We translate the results of a genome-wide high-throughput analysis into a tool that accurately predicts at presentation tumour growth and survival of patients with HCC. Design: Ultrasound surveillance identified HCC in 78 (training set) and 54 (validation set) consecutive patients with cirrhosis. Patients underwent two CT scans 6 weeks apart (no treatment in-between) to determine tumour volumes (V0 and V1 ) and calculate HCC doubling time. Baseline-paired HCC and surrounding tissue biopsies for microarray study (Agilent Whole Human Genome Oligo Microarrays) were also obtained. Predictors of survival were assessed by multivariate Cox model. Results: Calculated tumour doubling times ranged from 30 to 621 days (mean, 107±91 days; median, 83 days) and were divided into quartiles: ≤53 days (n=19), 54–82 days (n=20), 83–110 days (n=20) and ≥111 days (n=19). Median survival according to doubling time was significantly lower for the first quartile versus the others (11 vs 41 months, 42, and 47 months, respectively) (p<0.0001). A five-gene transcriptomic hepatic signature including angiopoietin-2 ( ANGPT2 ), delta-like ligand 4 ( DLL4 ), neuropilin (NRP)/tolloid (TLL)-like 2 ( NETO2 ), endothelial cell-specific molecule-1 ( ESM1 ), and nuclear receptor subfamily 4, group A, member 1 ( NR4A1 ) was found to accurately identify rapidly growing HCCs of the first quartile (ROC AUC: 0.961; 95% CI 0.919 to 1.000; p<0.0001) and to be an independent factor for mortality (HR: 3.987; 95% CI 1.941 to 8.193, p<0.0001). Conclusions: The hepatic five-gene signature was able to predict HCC growth in individual patient and the consequent risk of death. This implies a role of this molecular tool in the future therapeutic management of patients with HCC. Trial registration number: ClinicalTrials.gov Identifier: NCT01657695 .